PENGARUH DEFISIT ANGGARAN, INFLASI DAN KURS TERHADAP KUANTITAS UTANG LUAR NEGERI PEMERINTAH INDONESIA PERIODE 2001-2015 - Nurhalimah, Siti; Basri, Syafril; Mardiana, Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the budget deficit, inflation and the exchange rate against the quantity of foreign debt 2001-2015 period. The budget deficit as a variable (X1) inflation as a variable (X2) the exchange rate as a variable (X3) and the government foreign debt as a variable (Y). This research uses secondary data, this data is sourced from the Indonesian Financial Statistics Bank Indonesia and the Ministry of Finance of the Republic of Indonesia. The method in this research is quantitative by using statistical analysis and multiple linear regression equation coefficients calculation using SPSS 22. The result showed that based on the coefficient F calculated at 13.032 and F table 3.59 shows that F count is greater than F table variables simultaneously, which means the budget deficit, inflation and the exchange rate effect jointly to the quantity of government foreign debt 2001-2015 period.Results of the study also concluded that the value of the coefficient t for budget deficit of 2.716, the coefficient of - 0,809 t arithmetic inflation and exchange rate coefficient of -0.262 t while t table of 2.179. That shows the t variable budget deficit is greater than t table which means variable budget deficit significantly influence the quantity of foreign debt, while the variable inflation showed t count is smaller than t table which means that the variable inflation does not significantly influence the quantity of foreign debt government and variable exchhange rate shows the t less than t table which concluded that the exchange rate is not significant on quantity of government foreign debt 2001-2015 period.Keywords: the budget deficit, inflation, exchange rate, foreign debt